Persepsi Mahasiswa Farmasi, Keperawatan, Kesehatan Masyarakat, Gizi Dan Pendidikan Jasmani Terhadap Interprofessional Education (IPE) - Utami, Vitis Vini Fera Ratna; Satibi, Satibi; Kristina, Susi Ari; Prabandari, Yayi Suryo (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
The implementation of interprofessional education (IPE) is a key strategy to produce professionals who have the ability to collaborate with other professions or interprofessional collaboration (IPC) such as in pharmacy and other health sciences. The ability to collaborate between professions is important due to the changing role of pharmacists and increasingly integrated health services. Before implementing IPE, it is necessary to do an analysis of student perceptions of IPE and whether there are differences in the perceptions of students from different majors as a basis for developing IPE implementation. This research is a descriptive-analytical study conducted in a cross-sectional nature, in Faculty of Health Sciences (Fikes). The sampling technique used was a total sampling of 383 respondents, in 4th semester students, with respondent distribution in pharmacy majors (n=92), nursing majors (n=88), public health majors (n=95), nutrition majors (n=66) and majoring in physical education (n=42). The questionnaire used is the Interdisciplinary Education Perception Scale (IEPS) questionnaire. Then the total score was calculated based on the results of the questionnaire and continued with the Kruskal Wallis Test to find out the difference in scores between majors. Students in all majors have a good perception of IPE. The Nursing Department has the highest score (86.73% of the total score) and the Physical Education Department has the lowest score (83.61% of the total score). This shows that students in all majors have a positive perception of IPE. Based on the item questioner analysis, the point about being a professional who is reliable and can also be relied upon by other team members is something that needs to be improved. These two things need to be considered when applying IPE to learning activities.